Effects of different organic fertilizers on growth, yield and quality of Capsicum Annuum L. Var. Kulai (red chilli kulai) - Mohammad Moneruzzaman, Khandaker; Nashriyah, Mat; Fatin Rohani, .; Tahir, Dalorima (2017)
This study was designed to observe the effects of different organic fertilizers on growth, yield and quality of Capsicum annuum L. var Kulai (Red Chili Kulai). The field experiment was conducted at a green house of Faculty of Bioresources and Food Industry, Universiti Sultan Zainal Abidin (UniSZA), Tembila Campus, Kuala Terengganu. Performance of chilli plant was assessed by application of different organic fertilizer (vermicompost (VC),chicken dung (CiD), peat moss (PM), fermented fish waste (FFW), and cow dung (CoD)). The treatments were fitted in a Completely Randomized Design (CRD) design layouts. Data collected for growth, yield and quality performances included plant height, number of leaf per plant, leaf area, number of branch per plant, stomata conductance, chlorophyll content, number of flower bud per plant, number of fruit per plant, weight of fruit, length of fruit, diameter of fruit and number of seed per fruit. Based on the results obtained from this experiment, application of vermicompost and chicken dung shows highest growth, quality and yield performance. Control treatment (without organic fertilizer) showed the lowest growth, yield and quality response.